Revitalization as a synergistic effect - Szmygin, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
The development of modern cities is carried out in two main directions – expanding the suburban structures and restoring the life of the existing building areas. The growing problem that appears in discussions about the city is the revitalization, as evidenced by the fact of the entry into force October 9th 2015 the Act on revitalization. All definitions of revitalization emphasize its complexity and the fact that all activities must be carried out in an integrated and multidisciplinary way. Synergy is defined as an interaction of various factors, which effect is greater than the sum of separate actions. The alignment of those two definitions shows that revitalization is a synergistic effect. Effective revitalization is possible only when all the undertaken activities are coordinated. Therefore, all actions – urban, architectural, social, economic, etc. must be considered and treated as equally important for the proper functioning of the area. Article will present revitalization as a synergistic effect and showing at the same time that only the synergy of individual actions can lead to effective revitalization.